DETERMINATION OF GEOTHERMAL SYSTEM BOUNDARY USING SOIL AND SOIL-GAS SURVEY AND GEOMAGNETIC STUDY : A CASE STUDY FROM NORTH PATUHA GEOTHERMAL FIELD - TRI ABDULMALIK - NIM: 22615004, RULLY
Determination of geothermal system boundaries is usually carried out using geological and geochemical data of water, and magnetotelluric data by looking at the distribution of caprock from every depth of a geothermal field. This study will try to determine the geothermal system boundary using soil and soil-gas survey methods, and geomagnets. It is intended to develop geothermal system boundary research methods in the early stages of exploration where data are not yet widely available Geothermal systems generally have the characteristics of producing volatile gases (Hg and CO2) with high concentrations on the surface in areas with good permeability. Then, low values of magnetic data are generally part of the geothermal system. So that the expected boundary of a geothermal system can be determined. The study was carried out around Cimanggu - Rancaupas which is the boundary of the North Patuha Geothermal System. Soil and soil-gas surveys were taken within a distance between 500 meters of spacing on five tracks with a distance between 1000 meters of track. The measurement results showed the study area had concentration anomalies (Hg and CO2) above the background values scattered in the southern area of the study location. The acquisition of geomagnetic data is carried out on a 2.2 km track and 2 km long, with a 50 meter spacing extending from north to south. The geomagnetic data was then processed by daily correction, IGRF correction and reduce to poles/ equator for analysis. The results of the analysis showed that the area in the south has a low magnetic value and was different from the northern region. The low magnetic value and the high concentration of volatile gases (Hg and CO2) in the south of the study area are part of the Patuha Geothermal System which occupies an area of about 50%. Soil and soil-gas survey methods (Hg and CO2) as well as geomagnets in the North Patuha Geothermal Field can indicate the existence of geothermal system boundaries with results that were in accordance with previous research, so that this method can continue to be developed.